Evaluation of Safe Streets Treatment Option to Reduce Recidivism Among Repeat Drunk Driving Offenders. (December 2019) - Freiburger, Tina L.; Sheeran, Alyssa M.
Drinking and driving poses a significant issue in the United States. Repeat offenders are especially problematic as they are responsible for a high proportion of all drunk driving offenses and are more likely to continue in their drinking and driving behaviors. This study examines the effectiveness of the Safe Streets Treatment Options Program (SSTOP) in Outagamie County, Wisconsin, to reduce recidivism among repeat offenders. The results indicate that participants of SSTOP had significantly fewer convictions, fewer subsequent sentences to incarceration, were sentenced to fewer days incarcerated in jail for subsequent offenses, and were less likely to receive another Operating While Intoxicated (OWI) conviction than those in the comparison group. Policy implications and directions for future research also are discussed.